The Determinant Factors of Poverty in Eastern Indonesia: Evidence from 12 Provinces - Nur Rizqi Febriandika; Cahyaningtiyas Rahayu; Rahul Kumar (JEJAK: Jurnal Ekonomi dan Kebijakan, 2022)
This study aims to analyze the factors forming the number of poor people in Eastern Indonesia. Panel data regression was utilized as the analysis approach, with a cross-section comprising 12 provinces in Indonesia's Eastern Region from 2010 to 2018. This study will examine the effect of total government spending on education, government spending on health, labor force participation rate, regional minimum wage, investment, and the Gini index on poverty in Eastern Indonesia. The results showed that government spending on health and regional minimum wages had a negative effect on the number of poor people in Eastern Indonesia. The number of poor people in Eastern Indonesia will decrease if the realization of government spending on health and the determination of regional minimum wages increases. The increase in the realization of government spending in the health sector indicates that regional policies on the allocation of health spending have been carried out in a proportional, efficient, and effective manner so that they are right on target. Meanwhile, government expenditure on education, investment, labor force participation rates, and the Gini index has no effect on the number of poor people in Eastern Indonesia.